Playing for keeps. - Geer, Daniel E. (New York ACM, 2006)
Will security threats bring an end to general-purpose computing?
Keywords: Computing Milieux; Management of Computing and Information Systems; Security and protection; Software; Software engineering; Distribution, maintenance and enhancement; Metrics; Complexity measures; Security